HOW ASSESSMENTS OF TESTIMONIAL COMPETENCE PERPETUATE INEQUALITY AND DISCRIMINATION FOR PERSONS WITH INTELLECTUAL DISABILITIES: AN ANALYSIS OF THE APPROACH TAKEN IN SOUTH AFRICA AND ZIMBABWE (African Disability Rights Yearbook, 2021)
This paper examines the capacity to testify and access justice of witnesses with intellectual disabilities who have been sexually assaulted, focusing on the situation in South Africa and Zimbabwe. Through the rigid application of rules of criminal evidence and procedure to witnesses with intellectual disabilities, the criminal justice system sometimes perpetuates inequality and discrimination. The testimonial competence of witnesses with intellectual disabilities is often challenged due to the misconception that persons with intellectual disabilities do not make reliable witnesses in court. Using critical disability theory’s understanding of disability as resulting from the interactional process between a person with impairment and the environment, it is contended that incompetence to act as a witness is not inherent in the individual with impairment. The environment, which includes the rules of evidence and procedure, also plays a part yet it is often excluded from the assessment. It is argued that assessments of an individual’s ability should only be made for the purpose of determining what accommodations they need in order to give effective testimony in court.
Keywords: South Africa; Zimbabwe; capacity to testify and access justice; witnesses with intellectual disabilities